Identification of genetic modifiers of Parkinson's disease in yeast - Pui, Carmen Sze Min (Nanyang Technological University, 2023)
Alpha-synuclein (αSyn) is a primary constituent of Lewy bodies (LB), the hallmark pathological structures present in the brains of individuals affected by Parkinson's disease (PD). Despite the conventional understanding of fibrillar αSyn protein-protein aggregation in inclusion bodies, a growing body of evidence suggests that these structures represent clusters of cytoplasmic vesicles, with αSyn localized to the periphery of the vesicles. To understand more about the underlying mechanisms, yeast was utilized as a model to investigate various vesicular trafficking-related genes.